2015
DOI: 10.1111/jvs.12282
|View full text |Cite
|
Sign up to set email alerts
|

Responses of two contrasting saline‐alkaline grassland communities to nitrogen addition during early secondary succession

Abstract: Question (1) How do secondary successional dynamics differ in high and low saline‐alkaline grassland communities in semi‐arid lands; and (2) does nitrogen (N) enrichment promote plant secondary succession towards a perennial community under saline‐alkaline stress? Location Saline‐alkaline grassland in northeast China. Methods We selected two early successional communities differing in soil saline‐alkaline stress and floristic composition: one ‘high‐stress community’ co‐dominated by the annual grass Chloris vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…A possible reason could be that those pot-culture studies were conducted using sand as the substrate which contains no nutrition, therefore the N:P ratio in the substrate could be accurately controlled as same as the nutrient solution supplied. However, there always exist background interference of nutritional status under field condition (Bai et al, 2015). Though supply ratio did affect the soil N:P ratio significantly in our study, variations of soil N:P ratio are far slighter than the Table 4 Repeated measures analysis of variance for Species Richness and Shannon Index using Supply Level, Supply Ratio, Year, and all interactions as fixed-effects.…”
Section: Effects Of Overall Supply Level and Supply Ratio On Dominant Speciesmentioning
confidence: 70%
“…A possible reason could be that those pot-culture studies were conducted using sand as the substrate which contains no nutrition, therefore the N:P ratio in the substrate could be accurately controlled as same as the nutrient solution supplied. However, there always exist background interference of nutritional status under field condition (Bai et al, 2015). Though supply ratio did affect the soil N:P ratio significantly in our study, variations of soil N:P ratio are far slighter than the Table 4 Repeated measures analysis of variance for Species Richness and Shannon Index using Supply Level, Supply Ratio, Year, and all interactions as fixed-effects.…”
Section: Effects Of Overall Supply Level and Supply Ratio On Dominant Speciesmentioning
confidence: 70%
“…With succession proceeding, the patch size and the species richness increase, and the adjacent patches would meet and merge together to form larger but fewer patches. At the final stages, one or two perennial grasses such as L. chinensis should be dominant in these large patches (several hundred square meters) (Bai et al, 2015). Han et al (1996) found that the variation of species number with increasing area of patch shows a humped relationship.…”
Section: Study Area and Patch Characteristicsmentioning
confidence: 99%
“…First, an initial path model is constructed (Figure S1, Supporting Information). Predicted causal relations between variables were based on prior knowledge of the effects of additional N and water on the performance of plant communities (Bai et al ., ) and the correlation analysis. Then the effect of the relative strength of each independent variable on the dependent variable is estimated.…”
Section: Methodsmentioning
confidence: 99%